XX.YÜZYIL AMASYA TARİHİ VE İNANÇ COĞRAFYASI - ERDOĞAN, İSMAİL (Fırat Üniveristesi, 1996)
[Abstract Not Available]
The History and belief geography of Amasya in the 20 th. century
Keywords: Din; Religion; Tarih; History